The body creating theatrical narratives: influences of bodywork in the writing of an Amazonian dramaturgy - Martins, Benedita Afonso (2024)
This article aims to develop understandings about body-dramaturgy in a theatrical context based on situations experienced in the career of an actress-playwright-director-researcher who writes and directs plays in Belém do Pará since 2011. The premise is that the bodywork of Artists can directly influence dramaturgical development, since the body itself is a constant creator of narratives.  Seeking to expand the discussion, theoretical references and concrete examples are used to examine relevant concepts such as text-centrism, expanded dramaturgy and corporeality, which assist in a broader understanding of corporeal dramaturgy.